A sensor for monitoring the volume of nutrient in a solid substrate-based growth media by using electrochemical admittance spectroscopy - Sene, J. J.; Stradiotto, Nelson Ramos [UNESP]; Zeltner, W. A.; Anderson, M. A.; Zhou, W. J. (Elsevier B.V., 2002)
A sensor was fashioned to monitor the volume of nutrient in a solid substrate-based growth media by using electrochemical admittance spectroscopy. Several experimental parameters were investigated (i.e. The use of two- or three-electrode cells, the superficial area of the electrode, the amount of nutrient solution added to the growth media, and the influence of varying the dc and ac potential) to assess how these variables affect the admittance of the system. A linear correlation was observed between the maximum of the imaginary admittance and the volume of nutrient present. The response factor was 2.8 x 10(-5) S cm(-2) ml(-1) and the limit of detection (LOD) was 0.54 ml. The humidity of the growth media does not change the response of the nutrient toward the monitoring measurements. These results demonstrate that the volume of nutrient in this solid substrate-based growth media can be assessed using a ceramic sensor to measure the imaginary admittance. (C) 2002 Elsevier B.V. B.V. All rights reserved.
Keywords: sensor; admittance spectroscopy; solid substrate-based growth media; nutrient